Perbaikan Waktu Changeover Menggunakan Metode Single Minute Exchange Of Dies (Smed) Bagian Pencetakan Tabelt Pada Mesin Jc-16 Di PT. Samco Farma - ismail Fardiansyah; Lulu Azhara; Tri Widodo; irman maulana (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
The high changeover activity process for changing products causes the output produced by the loss Tabelt printing section to not meet the target, in data for September - December 2023 with total output only reaching 90.22%. This percentage is still less than the production standard set by the company which must reach 98%. Single Minute Exchange of Die (SMED) is a method from Lean Manufacturing that is used to reduce time in the setup/changeover process. Therefore, this research was carried out using the single minute exchange of dies (SMED) method. This research aims to determine the factors that influence the length of changeover time and make improvements using the Single Minutes Exchange of Dies (SMED) method. The total standard time for the changeover process obtained was 39581.7 seconds. before applying the SMED method, the changeover process had a total of 15 activities, with 13 internal activities and 2 external activities with an average total time of 39581.7 seconds. After implementing the SMED concept, it resulted in a total of 13 activities for the changeover process, 10 internal activities and 3 external. The simulation results of the proposed improvement have a total time of 30717.2 seconds with a reduction percentage of 22%. The results of the analysis using FTE changeover activities before and after implementing the SMED method, the total FTE was 1.57. Meanwhile, after implementing SMED, the total FTE was 1.2 with Normal information.Â Keywords: Changeover, Single Minute Exchange of Die (SMED), Stopwatch Time Study, Fishbone Diagram, Internal and external activities, FTE